2021
DOI: 10.1021/acsanm.1c00883
|View full text |Cite
|
Sign up to set email alerts
|

Sunlight-Driven Photocatalytic Degradation of Ciprofloxacin by Carbon Dots Embedded in ZnO Nanostructures

Abstract: Surface modification of ZnO nanoparticles (NPs) is considered as a key for enhanced sustained generation of reactive oxygen species (ROS) in the reaction medium for improving the photocatalytic degradation phenomenon. Here, we present a simple chemical method of synthesizing carbon dots (CDs) embedded on the surface of ZnO NPs denoted as ZnO/CD nanocomposites (NCs) as a photocatalyst for efficient sunlight-driven degradation of ciprofloxacin (CIP). The X-ray diffraction (XRD) and transmission electron microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(46 citation statements)
references
References 78 publications
1
45
0
Order By: Relevance
“…In the figure, the XRD pattern of pure ZnO clearly shows (100), (002), (101), (102), (110), (103), (200), (112), (201), (004) and (202) crystallographic planes of typical hexagonal ZnO lead-zincite structures (JCPDS file number 36-1451). 48,49 The pattern indicated that the as-synthesized ZnO has good crystalline properties. Besides, there are no extra diffraction peaks in the pattern so that the synthesized ZnO is relatively pure and free of extra impurities.…”
Section: Resultsmentioning
confidence: 99%
“…In the figure, the XRD pattern of pure ZnO clearly shows (100), (002), (101), (102), (110), (103), (200), (112), (201), (004) and (202) crystallographic planes of typical hexagonal ZnO lead-zincite structures (JCPDS file number 36-1451). 48,49 The pattern indicated that the as-synthesized ZnO has good crystalline properties. Besides, there are no extra diffraction peaks in the pattern so that the synthesized ZnO is relatively pure and free of extra impurities.…”
Section: Resultsmentioning
confidence: 99%
“…The flip side of smaller band gap materials is associated with increased probability of photoinduced charge carrier recombination. In addition, the other challenges in developing photocatalysts arise from manipulating band positions for improving redox conditions for generation of reactive oxygen species and photon absorptivity. , Recently, a lot of attention has been given toward development of smaller band gap metal oxides as photocatalysts, e.g., Co 3 O 4 , MoSe 2 , Bi 2 MoO 6 , Bi 2 WO 6 , WO 3 , BiOX (X= Cl, I, Br), , Ag 2 O, and g-C 3 N 4 , to utilize abundant sunlight for degradation of hazardous substances. Mostly, these studies are focused on photocatalytic dye degradation.…”
Section: Introductionmentioning
confidence: 99%
“…27–29 Large quantities of mulberry-based by-products of extraction residues are generated during the process, which could be envisaged for value-added secondary-utilization as green energy storage materials. 30,31 The total production of Ramulus mori in 2018 in China is in the scope of 2.844–3.555 million tons. 32 A large share of Ramulus mori is consumed by agro-industries where the disposal of waste Ramulus mori is a great issue.…”
Section: Introductionmentioning
confidence: 99%